The first report of colonic involvement of angioimmunoblastic T-cell lymphoma - Turan, İlker; Özsan, Nazan; Doğanavşargil, Başak; Davulcu, Eren Arslan; Bülbül, Hale (Turkish Journal of Gastroenterology, 2020)
Cite this article as: Turan İ, Özsan N, Doğanavşargil B, Arslan Davulcu E, Bülbül H. The first report of colonic involvement of angioimmunoblastic T-cell lymphoma. Turk J Gastroenterol 2020; 5: 413-4.